2013
DOI: 10.21157/j.med.vet..v7i2.2937
|View full text |Cite
|
Sign up to set email alerts
|

Kadar Asam Laktat Dan Derajat Asam Kefir Susu Kambing Yang Di Fermentasi Dengan Penambahan Gula Dan Lama Inkubasi Yang Berbeda

Abstract: ABSTRAKPenelitian ini bertujuan mengetahui kadar asam laktat dan derajat asam kefir susu kambing yang difermentasikan dengan penambahan gula dan waktu inkubasi yang berbeda. Penelitian ini menggunakan rancangan petak terbagi dalam rancangan acak lengkap menggunakan dua faktor perlakuan, penambahan gula dan lama inkubasi. Susu kambing yang telah dipasteurisasi dan ditambahkan starter kefir 3% dibagi menjadi 4 kelompok, yaitu P0 sebagai kontrol, dan PI, PII, PIII sebagai kelompok perlakuan (penambahan gula masin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 0 publications
0
4
0
6
Order By: Relevance
“…According Prastiwi, Bintoro, and Rizqiati (2018) that lactic acid bacteria in kefir grains will hydrolyze sucrose from molasses which will undergo the process of glycolysis to pyruvate and reduced by lactic acid bacteria to lactic acid and energy used for cell proliferation and growth of lactic acid bacteria. Based on this, it could be said that whey and molasses had sugar content such as lactose and sucrose which can be used as a good source of nutrition for lactic acid bacteria to grow and develop (Nursiwi et al, 2015;Rosiana, 2013;Rumeen et al, 2017) Yeast (Saccharomyces cerevisiae) The addition of grain kefir had a very significant effect (p <0.01) on the increase in yeast (Table 3). The treatment of adding 1-5% of kefir grain was very significant (p <0.01) increasing the amount of yeast compared to the control (without kefir grain).…”
Section: The Effect Of Adding Grain Kefir To Microbiology Lactic Acidmentioning
confidence: 99%
“…According Prastiwi, Bintoro, and Rizqiati (2018) that lactic acid bacteria in kefir grains will hydrolyze sucrose from molasses which will undergo the process of glycolysis to pyruvate and reduced by lactic acid bacteria to lactic acid and energy used for cell proliferation and growth of lactic acid bacteria. Based on this, it could be said that whey and molasses had sugar content such as lactose and sucrose which can be used as a good source of nutrition for lactic acid bacteria to grow and develop (Nursiwi et al, 2015;Rosiana, 2013;Rumeen et al, 2017) Yeast (Saccharomyces cerevisiae) The addition of grain kefir had a very significant effect (p <0.01) on the increase in yeast (Table 3). The treatment of adding 1-5% of kefir grain was very significant (p <0.01) increasing the amount of yeast compared to the control (without kefir grain).…”
Section: The Effect Of Adding Grain Kefir To Microbiology Lactic Acidmentioning
confidence: 99%
“…Menurut Liu (2004) susu kedelai mengandung oligosakarida yang sulit digunakan sebagai sumber energi. Hal ini sejalan dengan hasil penelitian Rosiana et al (2013) …”
Section: Total Bakteri Asam Laktatunclassified
“…The experimental work was performed using completely randomized design, consisting of two stages. First, the effect of incubation time (12,18, and 24 h) was studied, while the second stage was carried out to investigate the effect of different ratios (60:40; 50:50; 40:60). The results showed that addition of "Bedak Lotong" could enhance antibacterial activity.…”
Section: Introductionmentioning
confidence: 99%
“…Milk was sterilized and added with 10% kefir grain [10,13], followed with incubation of 37 °C for 12, 18, and 24 h [12]. The incubated milk was filtered to separate kefir grain.…”
Section: Introductionmentioning
confidence: 99%